Efektifitas Identifikasi Perubahan Tutupan Mangrove Menggunakan Citra Landsat-8 di Kecamatan Labuhan Maringgai, Lampung Timur - Pratama, Annisa Tias; Prasetio, Wiji; Prasetyo, Budhi Agung (J SIG (Jurnal Sains Informasi Geografi), 2025)
Mangrove forests play a crucial role in protecting coastlines, reducing CO2, and serving as natural resources. However, the growth of mangroves continues to decline due to human activities, necessitating studies to monitor mangrove coverage both directly and indirectly. This research aims to assess the effectiveness of identifying changes in mangrove coverage in Labuhan Maringgai District, East Lampung. The data used is Landsat-8 satellite imagery from the years 2019-2023. The method employed involves NDVI (Normalized Difference Vegetation Index) and EVI (Enhanced Vegetation Index) algorithms followed by random forest classification to determine mangrove and non-mangrove areas. Accuracy testing uses a confusion matrix with overall accuracy values and Kappa coefficient. In addition, the t-test was used to determine the effectiveness between the NDVI and EVI algorithms. The analysis results indicate a change in the area of mangrove coverage with annual increases in Labuhan Maringgai District. Sequentially from 2019 to 2023, using the NDVI algorithm showed values of 19%, 6%, 13%, and 7%, while the EVI algorithm showed values of 25%, 5%, 11%, and 8%. The accuracy test results produced have the highest average effectiveness in the NDVI algorithm with an overall accuracy of 95.4% and a Kappa coefficient of 0.87 compared to the EVI algorithm with an overall accuracy of 91.4% and a Kappa coefficient of 0.82. On the other hand t-test results indicate that utilize of the NDVI algorithm is more effective than EVI, with the correction value for the NDVI algorithm being 0.0077 compared to the correction value for the EVI algorithm being 0.1664.